Laminate film structures having barrier adhesive layer

By introducing a barrier adhesive layer into the laminated film structure, the problem of insufficient barrier performance of existing polymer film materials is solved, and the barrier performance is maintained or improved while reducing the number and thickness of the film layers, and the production cost is reduced.

JP2025020281AInactive Publication Date: 2025-02-12DOW GLOBAL TECHNOLOGIES LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024192502
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-09-22
Filing Date
2024-10-31
Publication Date
2025-02-12
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polymer film materials have insufficient barrier properties to oxygen and water vapor in packaging applications, resulting in vulnerability to packaging products, and existing methods for enhancing barrier properties often increase material thickness, weight and cost.

Method used

A laminated film structure containing a barrier adhesive layer is used to achieve similar barrier properties by replacing the conventional adhesive, reducing or removing part of the polymer film layer.

Benefits of technology

While maintaining or improving barrier properties, the number, thickness and weight of the film layer are reduced, production costs are reduced, and material recyclability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020281000008
    Figure 2025020281000008
  • Figure 2025020281000009
    Figure 2025020281000009
  • Figure 2025020281000010
    Figure 2025020281000010
Patent Text Reader

Abstract

To provide a laminate film structure in which the weight, thickness, and / or number of film layers has been reduced compared to existing laminated structures, while still achieving barrier properties, and to provide methods for forming laminate structures having a desired barrier performance.SOLUTION: The disclosed laminate film structures comprise films bonded together with an adhesive composition. The disclosed laminate film structures comprise films made from polymers and / or metallized polymers. Methods for forming laminate structures comprises: determining the desired barrier performance of the laminate structure; selecting a barrier adhesive; selecting two or more film layers, including at least a first film layer and a second film layer; applying the barrier adhesive on a surface of the first film layer, and bringing a surface of the second film layer into contact with the barrier adhesive applied on the surface of the first film layer, thereby forming the laminate structure having a desired barrier performance.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is a joint venture of U.S. Provisional Application No. 62 / 561,950, filed September 22, 2017. Claim the benefits of.

[0002] The present disclosure relates to laminated film structures that include an adhesive layer having barrier properties. The laminated film structure shown includes films bonded together by an adhesive layer. The adhesive layer has gas and / or moisture resistance, e.g., oxygen and / or water vapor transmission rate. The disclosed laminate film structure comprises a polymer and / or a metallized polymer. The present invention also includes a film produced thereby, while still achieving similar barrier properties. By using a barrier adhesive composition instead of a standard adhesive composition, the weight of the film layers is reduced. The present disclosure further provides a method for manufacturing a laminate having a barrier adhesive layer, the method comprising: Regarding the method of forming the layer structure, the method is to , for an existing laminate structure, the weight, thickness, and / or number of film layers in the laminate structure Allows for reduction. [Background technology]

[0003] Polymeric materials, and in particular films comprising polymeric materials, are widely used for packaging purposes. These polymeric materials are used in industrial and consumer applications as well as in the food and pharmaceutical industries. These and other applications involve protecting packaged products from oxygen (and Exposure to oxygen, nitrogen, nitrogen dioxide, and / or other gases as well as moisture can be highly undesirable. In particular, exposure to such gases and / or moisture may cause packaged products to deteriorate over time. Unfortunately, many polymer films are inherently gas and / or One approach to enhancing barrier properties that has been investigated is The method uses multiple layers of polymeric material and bonds the layers together with an adhesive to form a laminate. In some cases, the polymeric material layer and / or adhesive may be used to provide a barrier against Selected for its characteristics.

[0004] In recent years, high-level functionality of multi-layer films is required for long-term food preservation, and Gas barrier properties to prevent the intrusion of external oxygen to suppress oxidation, carbon dioxide barrier properties, and Currently, barrier properties against various odorous components are required. When applying the sealant, the polyolefin film typically used as the inner layer (sealant side) is These films have poor gas barrier properties and are difficult to apply a barrier to by coating or deposition. As a result, it is difficult to provide a rear function to the various films (polyester, etc.) used for the outer layer. Polyester resins such as polyethylene terephthalate (hereinafter abbreviated as "PET"), polyamide In many cases, the barrier function is imparted to .

[0005] In some cases, the film layer itself provides a barrier function. When coatings are used to provide a barrier function to One example of an aqueous coating material is chlorinated ethylenediaminetetraacetate, which exhibits excellent oxygen and water vapor barrier properties. However, there is a risk of dioxin formation when the material is incinerated during disposal. Further, there are problems associated with the use of vinylidene chloride, including polyvinyl alcohol resins. and ethylene-polyvinyl alcohol copolymers are also used as barrier coating materials. These materials have been reported to have good oxygen barrier properties under low humidity conditions, but they are poor at high humidity conditions. has poor oxygen barrier properties and is vulnerable to pinhole formation, which reduces its barrier properties. On the other hand, it is difficult to provide a gas barrier layer because it deteriorates the performance and shows poor boiling resistance and retort resistance. The films having a vapor-deposited layer of a metal such as aluminum are opaque. This means that you cannot see the contents of the container and it cannot be used in a microwave oven. Additionally, a vapor-deposited layer of a metal oxide such as silica or alumina may be provided as a gas barrier layer. Films having such properties are expensive, have poor flexibility and suffer from gas leakage due to cracks and pinholes. This results in large variations in barrier properties.

[0006] Furthermore, existing solutions for adding barrier functionality to laminate structures generally require multiple layers of the structure. Increasing the roughness (e.g., increasing the number of layers with specific barrier functions) and / or filtering By increasing the thickness of the rubber layer, the weight of the laminate structure is increased to provide a good barrier function. Increasing the complexity of these structures, either in the number of layers or layer thickness, increases the manufacturing This increases manufacturing costs.

[0007] Thus, the present invention includes a method for manufacturing a semiconductor device that includes a film layer made of a polymer and / or a metallized polymer. The laminated film structure includes a fluororesin, which still achieves similar barrier properties while still providing a It is desirable to reduce the weight, thickness, and / or number of film layers compared to existing laminate structures. It will become better.

[0008] Disclosed herein is a laminated film structure having a barrier adhesive layer. The laminated film structures are suitable for use, for example, in flexible packaging applications. The film structure comprises polymeric and / or metallized layers bonded together by a barrier adhesive layer. The polymeric film layers may include, whereby the weight, thickness, and / or number of the film layers may be , reduced, replaced, or eliminated by the inclusion of a barrier adhesive layer in the laminate film construction. In some embodiments, the disclosed laminate film structures are recyclable. The new laminated film structure uses standard adhesives and is equivalent to or better than the current laminated film structure. Desired barrier properties, such as control of gas and / or moisture permeability, can be achieved. However, the disclosed laminate film structure is less expensive than the costs required to manufacture current structures. This is beneficial in reducing the number of tests and / or process steps.

[0009] In some embodiments, the laminate film structure comprises a film layer and a surface of the film layer. In some embodiments, the film layer comprises a barrier adhesive layer disposed thereon. Styrene, polypropylene, polyethylene terephthalate, polyamide, polystyrene, Ethylene vinyl alcohol, polyvinyl chloride, cycloolefin copolymer, polyvinyl chloride , polymonochlorotrifluoroethylene, polyvinyl alcohol, citrine butadiene In some embodiments, the barrier adhesive layer is selected from the group consisting of a solvent-based The adhesives may include water-based adhesives, water-based adhesives, and / or solvent-free adhesives. In some embodiments, the disclosed laminate film structure comprises a film layer and a surface of the film layer. and a barrier adhesive layer disposed on the surface, the laminated film structure being in accordance with ASTM method D3985. Therefore, the measured value is 20ccO2 / m 2 / day or less. In one embodiment, the disclosed laminate film structure comprises a film layer and a The laminated film structure includes a barrier adhesive layer and is measured according to ASTM method F1249. 5gmH2O / m 2 / day or less water vapor transmission rate.

[0010] Methods for forming laminate structures having desired barrier properties are also disclosed. In some embodiments, the method includes determining the desired barrier performance of the laminate structure and selecting a barrier interface. selecting an adhesive and forming a film having at least a first film layer and a second film layer; Selecting the above film layers and applying a barrier adhesive onto the surface of the first film layer. and bonding a surface of the second film layer to a barrier adhesive applied on the surface of the first film layer. and contacting the coating with an agent to thereby form a laminate structure having the desired barrier properties. .

[0011] Also disclosed are articles comprising the disclosed laminate film structures. In some embodiments, The disclosed articles include, for example, flexible packaging, pouches, stand-up pouches, bags, etc. Included. [Brief description of the drawings]

[0012] Please refer to the attached drawings: [Figure 1] FIG. 1 is a schematic diagram of a current BOPP / metallized-BOPP laminate film structure and a new BOPP / BOPP laminate film structure using a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Diagram 2]FIG. 1 is a schematic diagram of a current BOPP / / metallized-BOPP / / PE laminate film structure and a new BOPP / / PE laminate film structure with a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Diagram 3] FIG. 1 is a schematic diagram of a current BOPP / / PE laminate film structure and a new BOPP / / PE laminate film structure with a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Figure 4] FIG. 1 is a schematic diagram of a current BOPP / / BOPP laminate film structure and a new BOPP / BOPP laminate film structure using a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Diagram 5] FIG. 1 is a schematic diagram of a current PET / / PE laminate film structure and a new PET / / PE laminate film structure using a barrier adhesive, where the current film structure and the new film structure have similar barrier properties. [Figure 6] FIG. 1 is a schematic diagram of a current PET / / PE / EVOH / PE laminate film structure and a new PET / / PE / EVOH / PE laminate film structure using a barrier adhesive. The current film structure and the new film structure have similar barrier properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In some embodiments, the disclosed laminate film structures include a polymer or metallized polymer. a film layer made from a polymer and a barrier adhesive layer disposed on a surface of the film layer In some embodiments, the first film layer, the second film layer, and the first Laminated film including a barrier adhesive layer disposed intermediate a film layer and a second film layer The structure is disclosed.

[0014] In some embodiments, the film layer is made of polyethylene, polypropylene, polyethylene Polyethylene terephthalate, nylon, polystyrene, and polyvinyl chloride. In some embodiments, the barrier adhesive layer is selected from the group consisting of solvent-based adhesives, water-based and / or solvent-free adhesives.

[0015] In some embodiments, the laminate film structure is measured according to ASTM method D3985. 20ccO2 / m 2 In some embodiments, the oxygen transmission rate is less than or equal to 1 / day. The layer film structure has a viscosity of 5 gmH2O / m2 measured according to ASTM method F1249 2 / days onwards It has a lower water vapor transmission rate.

[0016] In some embodiments, the barrier adhesive comprises an isocyanate component and an isocyanate In some embodiments, the isocyanate component comprises a single polyisocyanate-reactive component. In some embodiments, the polyisocyanate is an aliphatic polyisocyanate. In some embodiments, the polyisocyanate is a polymeric hexamer. Methylene diisocyanate (HDI trimer isocyanurate), methylene diphenyl diisocyanate socyanate, dicyclohexylmethane 4,4'-diisocyanate, and toluene diisocyanate In some embodiments, the isocyanate-reactive component is selected from , a hydroxyl-terminated polyester incorporated as a substantially miscible solid in a carrier solvent. The polyesters include esters having terminal hydroxyl groups and 2 to 10 carbon atoms. Polyesters are formed from a single linear aliphatic diol and a linear dicarboxylic acid. It has a number average molecular weight of 300 to 5,000, is solid at 25°C, and has a melting point of 80°C or lower. In some embodiments, the carrier solvent is ethyl acetate, methyl ethyl ketone, The solvent is selected from the group consisting of acetone, dioxolane, acetone, and combinations thereof. In an embodiment, the hydroxyl terminated polyester is a copolymer of a C3-C6 diol and adipic acid, an azetidinyl ester, and a hydroxyl terminated polyester. a dicarboxylic acid selected from arachidonic acid, sebacic acid, and combinations thereof; In some embodiments, the isocyanate-reactive component is an acrylate viscosity modifier. In some embodiments, the isocyanate component in the barrier adhesive further comprises a modifier. The weight ratio of the isocyanate-reactive components is 1:1 to 2:1.

[0017] In some embodiments, another filter made from a polymer or a metallized polymer. The adhesive layer is in contact with the film layer having a barrier adhesive layer disposed thereon, thereby A laminated film structure is created. The laminated film can be multi-layer or single layer. In embodiments, the disclosed laminate film structures still achieve similar barrier properties. While reducing the weight, thickness, and / or number of film layers compared to current laminate structures. By using a barrier adhesive layer instead of a standard adhesive, oxygen is prevented from passing through the laminate. and / or reduced moisture permeability. To better understand the potential applications of barrier adhesives, To achieve this, the test method is used to prepare samples that are tested to generate performance data. The permeability of the barrier adhesive is evaluated. The permeability of the barrier adhesive is derived from the data. potential cost savings by downgauging with a barrier adhesive instead of a standard adhesive Various film structures to take advantage of reduction, layer reduction, simplified construction, or sustainability A model is produced that allows the design of

[0018] Next, to predict the laminate performance with and without a barrier adhesive, Before creating a model to be used, the barrier performance of the barrier adhesive must first be quantified. To generate data to support the model, 25–35 wt. % crystalline polyethylene was used. ster resin, 0.25% defoamer 7R10 (acrylic copolymer with ethyl acetate), and and 64.75% by weight of urethane grade ethyl acetate. Several samples are prepared and tested. The polyester is an aliphatic isocyanate co-reactant. It is hardened with.

[0019] Samples were laminated in a LABO COMBI™ 400 laminator or a SU Using a PER COMBI 3000 laminator, the following Tables 1 and 2 were The barrier adhesive is then applied through a gravure cylinder to the filler. In Tables 1 and 2, the coated films are It is the first film listed for the construction of the 15BCM for the gravure cylinder. The adhesive is approximately 3g / m 2 applied at a coating weight of Then, when run on a LABO COMBI™ 400 laminator, the filter The system is set to 90°C in the first zone, 100°C in the second zone, and 110°C in the third zone. The mixture is then passed through a 3-zone oven set up in a SUPER COMBI™ 30 When run on the 00 laminator, the film is heated to 80°C in the first zone and 100°C in the second zone. The coated film passes through a two-zone oven set at 100°C. The film is then nipped to another film under a heated steel roll at a temperature of 90°C. The nip pressure is set at 40 psi. The laminate is then passed through a final chill roll at a temperature of 17° C. The laminate is then placed in a temperature controlled room and cured at 23°C and 50% relative humidity for 7 days. To transform.

[0020] The oxygen permeability of the sample laminate was measured according to ASTM method D3985 (using a coulometric sensor) The standard test method for oxygen gas transmission through the plastic films and sheets used was The moisture vapor transmission rate of the laminated structure is tested according to the method described in ASTM Method F124. The test is performed according to the method outlined in 9.

[0021] From the permeability data of the sample laminate structure, the permeability of the barrier adhesive itself can be determined. The transmission rate ("TR") of a vapor through a material is determined by the permeability ("P") (the rate at which it is transported through the medium). solubility of vapor in solid and diffusion of vapor when vapor is absorbed in solid) and path length or thickness of solid material (" The different thicknesses (L1, L2, etc.) and permeability can be described as a function of For a multi-layer solid with materials of different properties (P1, P2, etc.), the total water vapor transmission rate TR 合計 The following It can be explained as follows:

number

[0022] TR for oxygen and water vapor 合計 Experimental data on a series of experimentally fabricated laminated multilayers The disclosed and comparative adhesive compositions were used in layered configurations as detailed in Tables 1 and 2. Determine the average transmittance as a function of thickness. [Table 1] [Table 2]

[0023] From the analyzed samples, as shown in Tables 1 and 2, the barrier adhesive had a viscosity of 1.37ccO 2 / m 2 / day oxygen transmission rate and 1.20 gmH2O / m 2 / day water vapor transmission rate This particular barrier adhesive was used to predict the performance of various laminate structures. , used in the models discussed herein. However, oxygen permeability and water vapor permeability After the rate is determined, other barrier adhesives can be used in accordance with the present disclosure.

[0024] The estimated oxygen and water vapor transmission rates of the barrier adhesives were measured for various adhesives as shown in Tables 3 and 4. Used together with known transmittance values ​​for plastic films, the schematic diagrams shown in Figs. A laminated film structure is modeled, including: [Table 3] [Table 4]

[0025] For example, Figure 1 shows the current BOPP / met-BOPP laminate film structure and The schematic diagram of the new BOPP / BOPP laminated film structure using the current B adhesive is shown. OPP / met-BOPP laminated film construction is bonded to 20μm metal using standard adhesives The film contained 20 μm of BOPP laminated to a BOPP film with 14.9 ccO2 / m 2 The new BOPP / B with barrier adhesive has a calculated oxygen transmission rate of 100 / day. The OPP laminated film structure is laminated to another 20μm BOPP film using a barrier adhesive. The 20μm BOPP film is layered on the 2 / day calculated As is evident from FIG. 1 and the calculated oxygen permeability, the metallized BO The PP layer can be completely removed from the laminate structure while still achieving the same oxygen barrier performance. The current film and the new film are suitable for the same end use (e.g., packaging applications). is.

[0026] Figure 2 shows the current BOPP / met-BOPP / PE laminate film structure and burrs. The schematic diagram of the new BOPP / PE laminated film structure using the current BOPP / PE adhesive is shown. PP / / met-BOPP / / PE laminated film structure is 20μm thick with standard adhesive. 20μm BOPP film laminated to metallized BOPP film and additional Contains a 50μm PE film laminated to a metallized BOPP film using a semi-adhesive The current BOPP / / met-BOPP / / PE laminated film structure consumes 14.8ccO2 / m 2 New BOPP with barrier adhesive / / with a calculated oxygen transmission rate of 100 / day The PE laminate film structure was laminated to a 50μm PE film using a barrier adhesive Contains 20μm BOPP film, 13.6ccO2 / m 2 Calculated oxygen transmission per day As is evident from Figure 2 and the calculated oxygen transmission rates, the metallized BOPP layer , can be completely removed from the laminate structure while still achieving the same oxygen barrier performance. The old film and the new film are suitable for the same end uses (e.g., packaging applications).

[0027] Figure 3 shows the current BOPP / PE laminate film structure and the new barrier adhesive. The schematic diagram of the current BOPP / PE laminated film structure is shown. The film construction is made of 20μm BOP laminated to 70μm PE film using a standard adhesive. P film, 2.80 gmH2O / m 2 / day calculated water vapor transmission rate. New BOPP / PE laminated film structure with barrier adhesive It contains a 20μm BOPP film laminated to a 40μm PE film, and is 2.82 gmH2O / m 2 The calculated water vapor transmission rate is shown in Figure 3. As is evident from the transmittance, the thickness of the PE film is significantly increased while achieving the same moisture barrier performance. The current film and the new film are intended for the same end use (e.g., Suitable for packaging applications.

[0028] Figure 4 shows the current BOPP / / BOPP laminate film structure and the barrier adhesive used. A schematic diagram of the new BOPP / / BOPP laminated film structure is shown. The PP laminate film construction is laminated to a 20μm BOPP film using a standard adhesive 20μm BOPP film with 3.15gmH2O / m 2 / day calculated water vapor Air permeability. New BOPP / / BOPP laminated film structure using barrier adhesive is a 15μm BOPP laminated to a 15μm BOPP film using a barrier adhesive P film, 3.12 gmH2O / m 2 / day calculated water vapor transmission rate. As is evident from Figure 4 and the calculated water vapor transmission rate, the thickness of the BOPP film is The current film and the new film can be used to significantly reduce the moisture barrier while still achieving the same moisture barrier performance. The films are suitable for the same end uses (e.g., packaging applications).

[0029] Figure 5 shows the current PET / PE laminate film structure and the new barrier adhesive. A schematic diagram of the PET / PE laminate film structure is shown. Current PET / PE laminate film structure The construction is a 12μm PET film laminated to an 80μm PE film using a standard adhesive. 4gmH2O / m 2 Barrier adhesive with a calculated water vapor transmission rate of 100 / day. The new PET / PE laminated film structure with a 50μm barrier adhesive Contains 12μm PET film laminated to PE film, 4gmH2O / m 2 / day As is apparent from FIG. 5 and the calculated water vapor transmission rate, In addition, the thickness of the PE film can be significantly reduced while achieving the same moisture barrier performance. The line film and the new film are suitable for the same end use (e.g. packaging applications) .

[0030] Figure 6 shows the current PET / PE / EVOH / PE laminate film structure and barrier adhesion. The schematic diagram of the new PET / PE / EVOH / PE laminated film structure using the adhesive is shown. The PET / PE / EVOH / PE laminated film structure of the row uses a standard adhesive of 60μ It contains a 12μm PET film laminated to a 100μm EVOH film. PE / EVOH / PE laminated film structure is 1.60ccO2 / m 2 Calculated acid per day A new PET / PE / EVOH / PE laminated film using a barrier adhesive has excellent transparency. The film construction is a 12μm laminated to a 50μm EVOH film using a barrier adhesive. m of PET film, 1.63ccO2 / m 2 / day calculated oxygen transmission rate As is evident from Figure 6 and the calculated oxygen transmission rates, the EVOH film has the same oxygen permeability. The cost can be significantly reduced while still achieving the desired barrier performance. The old and new films are suitable for the same end uses (e.g., packaging applications).

[0031] Measured or calculated performance OTR and WVTR for each laminated film structure in Figures 1 to 6 The results are summarized in Tables 5 and 6 below. The first row under each row in the figure below lists the measured characteristics. The first row represents the properties, and the second row below each figure row represents the calculated properties. For example, using the rows in Figure 1 By doing so, the 20μ BOPP / 20μ MET BOPP structure row has the measured properties The rows identifying the 20μ BOPP / 20μ BOPP structures represent the calculated properties. [Table 5] [Table 6]

[0032] The structures tested and modeled, i.e., the structures shown in Figures 1-6, were fabricated in accordance with the present disclosure. These are not the only film structures and polymers that can be modified or replaced. Barrier performance may be affected by downgauging or replacement of other materials in the laminate structure, among other materials nylon, oriented polystyrene, and / or polyvinyl dichloride ("PVDC"), etc. Determine the desired barrier performance of the laminate film structure and determine the known / determinable Select a barrier adhesive with permeability and the permeability of the films used in the laminate film structure. By determining the number of films in the structure and / or the thickness of the films in the structure, By preparing a film structure that achieves similar barrier performance to existing films while reducing the This can be done.

[0033] Also disclosed are articles comprising the disclosed laminate film structures. In some embodiments, , articles include flexible packaging and stand-up pouches.

[0034] In addition to the above embodiments, many embodiments of specific combinations are within the scope of the present disclosure. some of which are explained below: Embodiment 1. A laminated film structure suitable for use in flexible packaging, comprising: A film layer; a barrier adhesive layer disposed on a surface of the film layer; The laminated film structure has a thermal conductivity of 20ccO2 / m2 measured according to ASTM method D3985. 2 Laminated film structure with oxygen permeability of less than 1000ppm / day. Embodiment 2. A laminated film structure suitable for use in flexible packaging, comprising: A film layer; a barrier adhesive layer disposed on a surface of the film layer; Laminated film structure has a thermal conductivity of 5 gmH2O / m2 measured according to ASTM method F1249 2 Laminated film structure with a water vapor permeability of less than 100% / day. Embodiment 3. A laminated film structure suitable for use in flexible packaging, comprising: a first film layer; a second film layer; and a barrier adhesive layer disposed intermediate the first film layer and the second film layer. fruit, The laminated film structure has a thermal conductivity of 20ccO2 / m2 measured according to ASTM method D3985. 2 Laminated film structure with oxygen permeability of less than 1000ppm / day. Embodiment 4. A laminated film structure suitable for use in flexible packaging, comprising: a first film layer; a second film layer; and a barrier adhesive layer disposed intermediate the first film layer and the second film layer. fruit, The laminated film structure has a thermal conductivity of 205 gmH2O / cm2 measured in accordance with ASTM method D3985. m 2 Laminated film structure with oxygen permeability of less than 1000ppm / day. Embodiment 5. A preceding or subsequent embodiment in which the barrier adhesive layer comprises a solvent-based adhesive. 10. The laminated film structure according to any one of the embodiments. Embodiment 6. A method according to any preceding or subsequent embodiment, wherein the barrier adhesive layer comprises a water-based adhesive. 13. The laminated film structure according to any one of claims 1 to 12. Embodiment 7. Any preceding or subsequent embodiment wherein the barrier adhesive layer comprises a solventless adhesive. 13. The laminated film structure according to claim 12 . Embodiment 8. The first film layer is made of polyethylene, polypropylene, polyethylene terephthalate. phthalate, nylon, polystyrene, and polyvinyl chloride. The laminate film structure of any of the preceding or subsequent embodiments, comprising a polymer. Embodiment 9. The second film layer is made of polyethylene, polypropylene, polyethylene terephthalate. phthalate, nylon, polystyrene, and polyvinyl chloride. The laminate film structure of any preceding or subsequent embodiment, comprising a polymer. Embodiment 10. The method according to claim 1, wherein the first film layer and the second film layer comprise the same polymer. 2. The laminate film structure of any of the preceding or subsequent embodiments. Embodiment 11. Any of the preceding or subsequent embodiments in which the laminate structure does not include a metallized film layer. 13. The laminated film structure according to any one of claims 1 to 12. Embodiment 12. A method according to claim 1, wherein the first film layer has a thickness of 25 μm or less, the preceding or following 20. The laminate film structure of any one of the following embodiments. Embodiment 13. A method for manufacturing a film having a thickness of 20 μm or less, the first film layer being a leading or trailing layer. 20. The laminate film structure of any one of the following embodiments. Embodiment 14. A method according to claim 1, wherein the first film layer has a thickness of 15 μm or less, the preceding or following 20. The laminate film structure of any one of the following embodiments. Embodiment 15. A method according to claim 1, wherein the second film layer has a thickness of 25 μm or less, the preceding or following 20. The laminate film structure of any one of the following embodiments. Embodiment 16. A method according to claim 1, wherein the second film layer has a thickness of 20 μm or less, the preceding or following 20. The laminate film structure of any one of the following embodiments. Embodiment 17. A method according to claim 1, wherein the second film layer has a thickness of 15 μm or less, the preceding or following 20. The laminate film structure of any one of the following embodiments. Embodiment 18. The barrier adhesive layer comprises: an isocyanate component including a single type of polyisocyanate; A hydroxyl-terminated polyether compound incorporated as a substantially miscible solid in a carrier solvent. and an isocyanate-reactive component comprising a polyester, A single linear aliphatic diol having a hydroxyl group and 2 to 10 carbon atoms. and a linear dicarboxylic acid, and the polyester has a number average molecular weight of 300 to 5,000. a preceding or succeeding amine having a quantity that is solid at 25°C and has a melting point of 80°C or less 3. The laminated film structure of any one of the embodiments. Embodiment 19. A laminated film structure according to any of the preceding or following embodiments. Includes: Embodiment 20. The article of any preceding or subsequent embodiment, wherein the article is a flexible package. . Embodiment 21. Any of the preceding or following embodiments, in which the article is a stand-up pouch. The item described. Embodiment 22. A method for forming a laminated structure having desired barrier properties, comprising: determining a desired barrier performance of the laminate structure; Selecting a barrier adhesive; Two or more film layers including at least a first film layer and a second film layer To choose, applying a barrier adhesive onto a surface of a first film layer; The surface of the second film layer is bonded to the barrier adhesive applied onto the surface of the first film layer. and contacting the resulting laminate structure with the desired barrier properties. . Embodiment 23. A third film layer is selected, and the surface of the third film layer is coated with the first film. the preceding or subsequent layer further comprising contacting the surface of the first or second film layer with the 2. The method according to any of the embodiments. Embodiment 24. The laminated film structure is an existing laminated structure having the same desired barrier performance. The method of any preceding or subsequent embodiment, wherein the thickness of the first and second electrodes is less than that of the first and second electrodes. Embodiment 25. A composition according to claim 20, wherein the desired barrier performance is measured according to ASTM method D3985. cO2 / m 2 In any of the preceding or following embodiments, the oxygen transmission rate is equal to or less than 1 / day. The method described. Embodiment 26. The desired barrier performance is determined according to ASTM method F1249 for 5 gm H2O / m 2 Any of the preceding or subsequent embodiments has a water vapor transmission rate of 10 / day or less. The method described above.

Claims

1. 1. A laminated film structure suitable for use in flexible packaging, comprising: A film layer; a barrier adhesive layer disposed on a surface of the film layer; The laminated film structure has a viscosity of 20 ccO measured according to ASTM method D3985. 2 / m 2 A laminated film structure with an oxygen permeability of less than 1000 g / day.

2. The first film layer is made of polyethylene, polypropylene, polyethylene terephthalate, A polymer selected from the group consisting of polystyrene, nylon, polyvinyl chloride, The laminated film structure of claim 1 , comprising:

3. The second film layer is made of polyethylene, polypropylene, polyethylene terephthalate, A polymer selected from the group consisting of polystyrene, nylon, polyvinyl chloride, The laminated film structure of claim 1 , comprising:

4. 10. The laminate film structure of claim 1, wherein the laminate structure does not include a metallized film layer. 。

5. The barrier adhesive layer comprises: an isocyanate component including a single type of polyisocyanate; A hydroxyl-terminated polyether compound incorporated as a substantially miscible solid in a carrier solvent. and an isocyanate-reactive component comprising a ester, wherein the polyester comprises A single linear aliphatic diol having a terminal hydroxyl group and 2 to 10 carbon atoms; and a linear dicarboxylic acid, the polyester having a number of from 300 to 5,000.

2. The composition according to claim 1, which has an average molecular weight of 1,0 ... is solid at 25° C., and has a melting point of 80° C. or less. The laminated film structure shown above.

6. An article comprising the laminated film structure of claim 1.

7. 1. A method for forming a laminate structure having desired barrier properties, comprising the steps of: determining the desired barrier performance of the laminate structure; Selecting a barrier adhesive; Two or more film layers including at least a first film layer and a second film layer are To choose, applying the barrier adhesive onto a surface of the first film layer; The surface of the second film layer is coated with the and contacting said laminate structure with a barrier adhesive, thereby forming said laminate structure with the desired barrier properties. A method comprising:

8. The laminated film structure is thicker than existing laminated structures having the same desired barrier properties.

8. The method of claim 7, wherein the insulating layer has a thickness less than 100 nm.

9. The desired barrier performance is 20 ccO 2 / m 2 8. The method of claim 7, wherein the oxygen transmission rate is less than or equal to 100 / day.

10. The desired barrier performance is 5 gmH 2 O / m 2 8. The method of claim 7, wherein the water vapor transmission rate is less than or equal to 100 / day.

Citation Information

Patent Citations

  • Lamination of polymer film

    JP1999148066A

  • Oxygen-barrier film and adhesive

    WO2011162160A1